The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1007/s12088-016-0625-1
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial Virulence Factors: Secreted for Survival

Abstract: Virulence is described as an ability of an organism to infect the host and cause a disease. Virulence factors are the molecules that assist the bacterium colonize the host at the cellular level. These factors are either secretory, membrane associated or cytosolic in nature. The cytosolic factors facilitate the bacterium to undergo quick adaptive-metabolic, physiological and morphological shifts. The membrane associated virulence factors aid the bacterium in adhesion and evasion of the host cell. The secretory … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
79
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 146 publications
(102 citation statements)
references
References 75 publications
2
79
0
1
Order By: Relevance
“…Virulence is described as the ability of a pathogen to infect and cause disease in a host, and bacterial virulence factors, such as toxins, enzymes, as well as the factors involved in biofilm formation, can facilitate the infection of host organisms by bacteria. The expression of virulence genes is mainly regulated by quorum sensing (QS) (Sharma et al., 2017; Vestergaard & Ingmer, 2019). The antivirulence strategy aims at neutralizing or suppressing the production of virulence factors that are essential for bacterial pathogenicity rather than for their survival, thus imposing much less pressure for bacteria to develop drug resistance (Lee, Lee, Kim, Cho, & Lee, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Virulence is described as the ability of a pathogen to infect and cause disease in a host, and bacterial virulence factors, such as toxins, enzymes, as well as the factors involved in biofilm formation, can facilitate the infection of host organisms by bacteria. The expression of virulence genes is mainly regulated by quorum sensing (QS) (Sharma et al., 2017; Vestergaard & Ingmer, 2019). The antivirulence strategy aims at neutralizing or suppressing the production of virulence factors that are essential for bacterial pathogenicity rather than for their survival, thus imposing much less pressure for bacteria to develop drug resistance (Lee, Lee, Kim, Cho, & Lee, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…For the purpose of this review, genes which are involved in the production of pathogenicity and virulence factors produced are themselves called pathogenicity and virulence factors. Pathogenicity and virulence-associated with plant pathogens are made possible by the secretion of pathogenicity and virulence factors which are molecules that help the pathogen colonize the plant [42,43]. For the purpose of this review, genes which are involved in the production of pathogenicity and virulence factors produced are themselves called pathogenicity and virulence factors.…”
Section: Pathogenicity and Virulence Factors Of Plant Pathogensmentioning
confidence: 99%
“…The protein region of the oomycete Phytophthora family of the phytotoxinlike scr74 gene, the C-terminal of Phytophthora RXLR effector paralogues and a single amino acid polymorphism in the Phytophthora EPIC1 effector were related to the capacity to specialize in a fresh host [48][49][50]. Stukenbrock and McDonald [51] also reported polymorphism data showing the spread Pathogenicity and virulence-associated with plant pathogens are made possible by the secretion of pathogenicity and virulence factors which are molecules that help the pathogen colonize the plant [42,43]. For the purpose of this review, genes which are involved in the production of pathogenicity and virulence factors produced are themselves called pathogenicity and virulence factors.…”
Section: Pathogenicity and Virulence Factors Of Plant Pathogensmentioning
confidence: 99%
“…Without cytosolic delivery by GNLY, the Gzms can only target secreted or externally exposed bacterial proteins, known to be involved in virulence (Desvaux and Hebraud, 2006;Sharma et al, 2017). When we treated Listeria monocytogenes (Lm), strain10403S, supernatants with GzmB, we found that two major virulence factors, listeriolysin O (LLO) and the invasion associated protein p60 (Iap), were efficiently degraded by the protease (Figure S1A).…”
Section: Gzmb Cleaves Multiple Secreted or Membrane-exposed Bacterialmentioning
confidence: 99%